Prosodic organization of English folk riddles and the mechanism of their decoding - Taranenko, Larysa (LingBaW. Linguistics Beyond and Within, 2016)
The paper advances a cognitive model representing a creative mechanism of riddle decoding by its recipient, which serves as a theoretical and methodological ground for the experimental phonetic study of prosodic means that organize the text of a riddle. Within the process of cognitive model formation the author performs a conceptual analysis of the riddle compositional structure, presented as a systemic algorithmic scheme. It is confirmed that a characteristic feature of a folk riddle is its division into two elements: the first one is the description of an object, further differentiated into “topic” and “commentary”, while the second one is the riddle answer, or solution, generated directly in the recipient’s mind as a result of his/her mental activities. The carried out auditory analysis proves that such a limitation of the riddle’s structure is compensated by a set of prosodic means and their specific interaction, which trigger creative and cognitive processes in the recipient’s mind aimed at searching for the riddle solution.